Identification and Antimicrobial Susceptibility Testing of Staphylococcus Aureus from Clinical Samples of Tertiary Care Centre, North India (International Journal of Scientific Research in Science and Technology, 2024)
Staphylococci are contributors of the Micrococcaceae family. Staphylococcus aureus is the most common type of bacteria which causes infections in the humans. They are classically taken into consideration extracellular, pyogenic pathogens due to their capacity to set off abscess formation. The microorganisms are non-motile and generally tend to develop in clusters. They are extraordinarily hardy and may continue to exist for extended durations of time on environmental surfaces. Staphylococci are identified in medical samples with the aid of using Gram stain and their function morphology – Gram positive cocci in grape-like clusters. They shape spherical frequently beta-hemolytic colonies on agar. It is characterized by the presence of the bacteria in different samples collected from different departments and the use of different antibiotic drugs and other medicines have increased the rate of infections. Some of the other risk factors includes the advanced ages and hospitalization. Staphylococcus aureus can be of different types like MRSA, MSSA, VRSA etc. Staphylococcus can cause infections in different ages it can infect child also or adult also. Different types of samples of Staphylococcus aureus can be identified using MALDI-TOF, MICROSCAN and BD PHOENIX and their interpretation of the antimicrobial susceptibility test can be given. Staphylococcus aureus is a major bacterial human pathogen that causes a wide variety of harmful diseases to the clinical manifestations. Infections caused by this bacterium are commonboth in community as well as hospital settings and treatment of the diseases caused by this remains challenging to manage. Because due to the emergence of its multi-drug resistant strainssuch as MRSA. Different drugs were used like Amp/Sulbactam, Ampicilin, Ceftriaxone, Ciprofloxacin, Clindamycin, Daptomycin, Erythomycin, Linezolid, Oxacillin, Rifampin, Synercid, Tetracycline, Teicoplanin, Vancomycin, Penicillin. The antimicrobial susceptibility test was done and their resistance percentage is calculated.